(untitled) (Lundiana: International Journal of Biodiversity, 2008)
Specimens recently recorded as belonging to a species widely distributed in the Neotropical Region, Eufriesea ornata (Mocsáry, 1896) (Hymenoptera: Apidae), in the Brazilian Atlantic Rain Forest, have been shown to belong to a distinct species, Eufriesea atlantica sp. n., described in the present study.